2023
DOI: 10.3390/ijerph20021193
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-Counter Medication Use among Parents in Saudi Arabia

Abstract: Introduction: Self-medication is a growing public health concern worldwide. Studies have shown a gap between best practice and the current practice of using over-the-counter (OTC) medications. Despite being a well-recognised problem in Saudi Arabia, few studies have investigated OTC medication use in Saudi Arabia. Therefore, this study aimed to investigate the attitudes and knowledge of parents regarding OTC medication use in the Jeddah region, Saudi Arabia. Method: A cross-sectional study was carried out via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…In the earlier findings, poor knowledge levels about self-medication were mentioned, which corresponded to the findings of other international studies done with university students [ 22 - 24 ]. Despite the misuse of OTC medications and the resulting medicine-related issues, their number in the market and the prevalence of usage are escalating in certain countries [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the earlier findings, poor knowledge levels about self-medication were mentioned, which corresponded to the findings of other international studies done with university students [ 22 - 24 ]. Despite the misuse of OTC medications and the resulting medicine-related issues, their number in the market and the prevalence of usage are escalating in certain countries [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Across the world, the practice of using over-the-counter (OTC) drugs for self-medicating is more prevalent than the use of prescription drugs [1][2][3]. According to the World Health Organization (WHO) specifications, both developed and developing countries reveal that the practice of self-medication has become an essential part of daily life and plays a vital part in the healthcare system as the socio-economic status and education levels of the population continue to improve [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…24 Educational campaigns for responsible self-medication should be strengthened by encouraging community pharmacies to take the initiative to actively guide and educate patients about the proper use of over-the-counter medications. 25 Continuous efforts should be made to create age-appropriate formulations that offer both dosing flexibility and palatable taste. There is still room for improvement in terms of improving parents' health performance and increasing their knowledge of some antibiotic-related health issues.…”
Section: Discussionmentioning
confidence: 99%
“…Educational campaigns for responsible self-medication should be strengthened by encouraging community pharmacies to take the initiative to actively guide and educate patients about the proper use of over-the-counter medications. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Study findings in the Dammam district revealed that more than half of the people (66%) lacked appropriate understanding regarding OTC pharmaceuticals. Purchases of OTC medications from community pharmacies were rather popular in the Qassim region (75%), with the most frequent reason for doing so being the renewal of a prior prescription from a medical professional (30%) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%